Molecular Bases for the Regulation of NKG2D Ligands in Cancer - Huergo-Zapico, Leticia; Acebes-Huerta, Andrea; López-Soto, Alejandro; Villa-Álvarez, Mónica; Gonzalez-Rodriguez, Ana Pilar; Gonzalez, Segundo (Frontiers in Immunology, 2014)
NKG2D is an activating receptor expressed by NK and T cells primarily involved in the elimination of transformed and infected cells. NKG2D ligands are self-proteins restrictedly expressed in healthy tissues, but induced in response to signaling pathways commonly associated with transformation. Proliferative, tumor suppressor and stress signaling pathways linked to the tumorigenic process induce the expression of NKG2D ligands, initiating an immune response against the incipient tumor. Nevertheless, the activity of NKG2D ligands is counter-regulated in vivo by the immunoediting of cancer cells, resulting in the expression of multiple mechanisms of immune evasion in advanced tumors. The redundancy of NKG2D ligands, besides increasing the complexity of their regulation, may impair the generation of these immune evasion mechanisms. In this review, we attempt to integrate the mechanisms and pathways involved in the regulation of NKG2D ligand expression in cancer.